Pengaruh Media Pembelajaran Visual Terhadap Motivasi Belajar Pendidikan Agama Kristen siswa kelas IX Di SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Lastri Novia Sitompul; Oloria Malau; Dorlan Naibaho; Sabar Rudi Sitompul; Franskoy Rio Naibaho; Andrianus Nababan; Malani Simanungkalit (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to find out how much positive and significant the influence of visual learning is on the learning motivation of Christian religious education students in IX SMP Negeri 4 Tarutung for the 2023/2024 academic year. The research method used is a quantitative method with descriptive statistics. The population is all 160 class IX students of SMP N 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Protestant Christians and a sample of 40 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 52 items, namely 24 items for variable North Tapanuli Regency for the 2023/2024 Academic Year, proven through the following data analysis: 1) Test the analysis requirements: a) positive relationship test obtained a value of rxy = 0.589 > Itabel(-0.05,n=40) = 0.312. b) Testing a significant relationship obtained a t value of 4.498 t table (= 0.05, dk = n-2-38) = 2.021. 2) Influence test: a) Regression equation test, obtained regression equation Y=42.15+0.65X = 42.15 +0.65X, b) Regression coefficient of determination test (r²) = 34.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=23, dk denominator-n-2-40-2-38) namely 20.21 > 1.51. Thus Ha is accepted and Ho is rejected.